2010
DOI: 10.2527/jas.2009-2537
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis of 5 swine breeds in the United States and the implications for genetic conservation1

Abstract: Globally, genetic diversity of livestock populations is contracting. Knowing the true extent of the contraction is needed to develop effective conservation strategies. Although contractions of genetic diversity have been documented at the breed level, little within breed documentation has occurred. This situation is no different for US swine breeds. Therefore, the objective of this study was to establish an inbreeding baseline for 5 pig breeds via pedigree records extracted from purebred registrations to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 12 publications
9
45
2
1
Order By: Relevance
“…In any case, the general scenario of the Gochu Asturcelta pig breed can hardly be compared with others in the literature. Indeed, pedigree depth is substantially lower than the depths reported for the well-established commercial pig breeds of Canada and the United States (Melka and Schenkel 2010;Welsh et al 2010) which included, in general, more than 11 complete generation equivalents. Nevertheless, the mean inbreeding in the breed is up to seven-fold higher than that reported for these American pig populations, ranging from 0.032 to 0.078.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In any case, the general scenario of the Gochu Asturcelta pig breed can hardly be compared with others in the literature. Indeed, pedigree depth is substantially lower than the depths reported for the well-established commercial pig breeds of Canada and the United States (Melka and Schenkel 2010;Welsh et al 2010) which included, in general, more than 11 complete generation equivalents. Nevertheless, the mean inbreeding in the breed is up to seven-fold higher than that reported for these American pig populations, ranging from 0.032 to 0.078.…”
Section: Discussionmentioning
confidence: 74%
“…Average generation interval computed for Gochu Asturcelta (1.8 years) is consistently the same as the others previously reported in the literature for non-endangered pig breeds. Melka and Schenkel (2010) reported generation intervals of 1.6 and 1.7 years for Canadian Duroc and Landrace, respectively; Welsh et al (2010), analyzing the pedigree of five United States pig breeds, reported generations intervals ranging from 1.7 (Berkshire) to 2.2 (Yorkshire) years; Tang et al (2013), in three cosmopolitan pig breeds imported into China, reported generation intervals ranging between 1.8 and 1.9 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideal inbreeding rates vary between 0.05 (Nicholas, 1989) and 0.01 (FAO, 1998) per generation. This would indicate that current levels are favorable for the Pantaneiro horse but it should be remembered that registration is on the increase and Welsh et al (2010) also showed low initial inbreeding for commercial pig breeds in the US, but in later generations it increased to high levels. The predicted curve in the present study (Figure 3) shows that inbreeding cannot be ignored if conservation issues are to be met, especially with closure of the herd book.…”
Section: Discussionmentioning
confidence: 99%